COMPETENCY ACQUISITION, DIFFICULTY AND PERFORMANCE OF FIRST YEAR COLLEGE STUDENTS IN MATHEMATICS IN THE MODERN WORLD (MITMW) - Roman, Adriel G.; Villanueva, Rogacion U. (Universitas Ahmad Dahlan, 2019)
Mathematics in the Modern World (MITMW) is one of the general education subjects taught in the new college curriculum in the Philippines. In this study, the self-assessment of students on their acquisition of the competencies set in the MITMW are being described as well as the extent of difficulties and performance. Using descriptive correlational research design, this study hypothesized that the perceived extent of acquisition of the first year college students on the competencies intended for Mathematics in the Modern World and their extent of difficulties experienced provide significant relationship to their performance. Two hundred seventy-one (271) first year college students were surveyed using validated questionnaires. Results revealed that the first year college students have higher extent of acquisitions on the competencies set in the MITMW (knowledge, values, and skills). Students experienced slight difficulties on the different topics of MITMW with satisfactory performances in the subject. Finally, the study concluded that acquired competencies and difficulties are both significantly related to students? performance in MITMW.